1 - 1/6 = 1/1 - 1/6 = 6/6 - 1/6 = (6-1)/6 = 5/6.
6
To calculate 2/3 + 1/6 + 1/6, we first need to find a common denominator for the fractions, which in this case is 6. Then, we convert each fraction to have a denominator of 6: 2/3 becomes 4/6, and 1/6 + 1/6 remains as 1/6 + 1/6. Adding these fractions together gives us 4/6 + 1/6 + 1/6 = 6/6, which simplifies to 1. Therefore, the calculation of 2/3 + 1/6 + 1/6 is equal to 1.
360
1 1/6= (6 + 1)/6= 7/6 in improper fraction
1 - 1/6 = 1/1 - 1/6 = 6/6 - 1/6 = (6-1)/6 = 5/6.
6
The chances are (1/6) x (1/6) x (1/6)The chances are (1/6) x (1/6) x (1/6)The chances are (1/6) x (1/6) x (1/6)The chances are (1/6) x (1/6) x (1/6)
To calculate 2/3 + 1/6 + 1/6, we first need to find a common denominator for the fractions, which in this case is 6. Then, we convert each fraction to have a denominator of 6: 2/3 becomes 4/6, and 1/6 + 1/6 remains as 1/6 + 1/6. Adding these fractions together gives us 4/6 + 1/6 + 1/6 = 6/6, which simplifies to 1. Therefore, the calculation of 2/3 + 1/6 + 1/6 is equal to 1.
360
(1) - (1/3 + 1/6 + 1/6) = (1) - (2/6 + 1/6 + 1/6) = (1) - (4/6) = (6/6) - (4/6) = (2/6) = 1/3
1 1/6= (6 + 1)/6= 7/6 in improper fraction
1 5/6 = (1×6+5)/6 = 11/6 → 1/(1 5/6) = 1/(11/6) = 6/11
12
There are 6 one sixths in 1. 1 divided by 1/6 = 1 ÷ 1/6 = 1 * 6/1 = 6 1/6 is the reciprocal of 6. So any number multiplied by its reciprocal gives 1.
The sum of 5/6 and 1/3 = 1 1/6
Infinitely many. 1*6 1*1*6 1*1*1*6 (-1)*(-6) (-1)*(-1)*(-1)*(-6) 1*1*(-1)*(-6) and all those are using only 1 an 6. You could also use 10 and 0.6, 2 and 3 etc.